Efficiency of application of cardiotraining’s facilities in the increase of the cardiovascular system’s functional state of judoists 7–12 years - Верітов Олександр Ігорович (Oleksandr Veritov) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: to give the estimation of efficiency of application of cardiotraining facilities in the increase of the cardiovascular system’s functional state of young judoists 7–12 years. Materials and Methods : in research participated 60 judoists 7–12 years. There was used the method of variation pulsometre and computer program "SHVSM-іntegral" for the estimation of the cardiovascular system’s functional state. Results: the positive dynamics of cardiovascular system’s indexes of the judoists 7–12 years under act of cardiotraining facilities. Conclusions: the use of cardiotraining facilities in the training process of young judoists go to the reliable increase of the cardiovascular system’s functional state of their organism